2018
DOI: 10.24925/turjaf.v6i11.1653-1661.2181
|View full text |Cite
|
Sign up to set email alerts
|

Consumers‘ Bread Consumption Habits and Waste Status: Hatay/Turkey Example

Abstract: In this study, it was aimed to determine the reasons for the waste of bread among consumers in Hatay province and what should be taken for the elimination of these causes. The subjects of this study were the data obtained from 406 consumers selected from the city center. The data were obtained through face to face interviews during the period of May-2017. In the questionnaire, there were questions towards determining the bread consumption habits, consumption preferences and bread waste levels along with the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…These inferences, Demirtaş et al (2018), Sarica et al (2021), and Dong and Karboune (2021), are also like the findings and literature reports.…”
Section: Correlation Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…These inferences, Demirtaş et al (2018), Sarica et al (2021), and Dong and Karboune (2021), are also like the findings and literature reports.…”
Section: Correlation Analysissupporting
confidence: 88%
“…However, in the staleness of bread, evaluation forms may affect human health, especially when it comes to microbial activities, consumption of bread, feeding to animals rather than human consumption, etc. These interpretations are approved by Demirtaş et al (2018), Sarica et al (2021), and Dong and Karboune (2021).…”
Section: Table 11mentioning
confidence: 92%
See 1 more Smart Citation
“…Bread is the primary foodstuff in daily nutrition. Turkey is among the first countries in the world with high consumption of bread such that 199.6 kg/year consumption per person was recorded in the book Guinness World Records in the year 2000 [41]. Demirtas et al [42] revealed in 2018 a bread consumption of 101.5 kg/year for people living in Turkey.…”
Section: Preferences For Breadmentioning
confidence: 99%
“…The average daily bread consumption in Iran is about 320 g, up to nearly 117 kg per capita annually [ 4 ], almost twice that of European countries [ 5 ]. There are many factors involved in reducing the quality of bread and increasing its waste, including the quality of the raw material [ 6 8 ], the process of making bread [ 7 ], the knowledge and attitude of bakers and consumers about baking, consuming, and storing bread [ 9 , 10 ]. The bread quality plays an essential role in people’s health and the national economy, and improving its situation requires serious attention.…”
Section: Introductionmentioning
confidence: 99%